Perforin/granzyme-dependent and independent mechanisms are both important for the development of graft-versus-host disease after murine bone marrow transplantation. - Graubert, T A (1997)
Graft-versus-host disease (GvHD) is the major limiting toxicity of allogeneic bone marrow transplantation. T cells are important mediators of GvHD, but the molecular mechanisms that they use to induce GvHD are controversial. Three effector pathways have been described for cytotoxic T lymphocytes: one requires perforin and granzymes, the second Fas (APO-1; CD95) and its ligand. Thirdly, secreted molecules (e.g., TNF-alpha, gamma-IFN) can also mediate cytotoxicity. Together, these mechanisms appear to account for virtually all cytotoxicity induced by activated CTL in standard in vitro lytic assays. Using transplants across histocompatibility barriers, we were able to analyze the contributions of these effector molecules to cell-mediated cytotoxicity in vivo in a GvHD model. We found that Fas ligand is an important independent mediator of class II-restricted acute murine GvHD, while perforin/granzyme-dependent mechanisms have only a minor role in that compartment. In contrast, perforin/ granzyme-dependent mechanisms are required for class I-restricted acute murine GvHD, while Fas ligand is not. The perforin/granzyme pathway may therefore represent a novel target for anti-GvHD drug design. In support of this approach, we provide additional data suggesting that specific perforin/granzyme inhibitors should not adversely affect hematopoietic recovery after transplantation.